Improving durability of reinforced concrete structures by recycling wet‐ground MSWI bottom ash. Issue 6 (31st March 2016) - Carsana, M.; Gastaldi, M.; Lollini, F.; Redaelli, E.; Bertolini, L.
Abstract : Municipal solid waste incineration (MSWI) generates high amounts of bottom ash that, after grinding, could be used as mineral addition for concrete. Wet grinding of the bottom ash can prevent the risk of deleterious expansion due to hydrogen evolution, associated to the presence of metallic aluminium. The pozzolanic behavior of the bottom ash may improve concrete resistance to the penetration of aggressive species. Advantages of recycling wet‐ground MSWI bottom ashes may even be higher when self‐compacting concrete (SCC) is used, which requires large quantity of fine powders (usually more than 500 kg/m 3 ) to prevent segregation of the fresh mix. This paper describes the results of a research aimed at investigating the use of wet‐ground MSWI bottom ashes as mineral additions for the production of self‐compacting concrete. Several types of mineral additions (MSWI bottom ash, coal fly ash, and ground limestone) were used in replacement of 15, 30, and 45% of Portland cement. The results showed that the MSWI ash, added to the mix as a fine slurry obtained by wet‐grinding, led to the production of SCC concrete with compressive strength and resistance to chloride and carbonation similar, or even better, than those of concrete with same amount of coal fly ash. Abstract : Bottom ash produced by municipal solid waste incineration, after wet grinding, is proposed as mineral addition for self‐compacting concrete. The alkaline slurry allows quick corrosion of fine aluminium particles present in the ash, thus preventing the deleterious expansion of concrete during setting due to hydrogen evolution. The pozzolanic properties of this recycled waste improve durability‐related properties of concrete.